TANGGUNG JAWAB PELAKU USAHA LAUNDRY TERHADAP KONSUMEN MENURUT HUKUM PERJANJIAN DI KOTA PEKANBARU - Siska, Nia; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In this modern era, with human activity increasingly increasing, activities such aswashing clothes are no longer carried out alone. This has led to the emergence of servicebusinesses that are used as business actors to facilitate human work, one of which islaundry or laundry services. Laundry is a business that offers services in terms ofwashing clothes with special methods. From these activities, the emergence of how tocarry out the responsibilities of laundry entrepreneurs to consumers in Pekanbaru City.The formulation of the problem in this study is how the implementation of the rights andobligations of laundry businesses to consumers in Pekanbaru and what are the barriersto the implementation of the responsibilities of laundry businesses to consumers inPekanbaru.The purpose of this study is First, to be able to explain the rights and obligationsof laundry owners to consumers in the city of Pekanbaru. Second, to find out theobstacles in the implementation of the responsibility of the owner of the laundry toconsumers in the city of Pekanbaru. The type of research I use is a type of sociologicalresearch. The research location that is the object of this research is that laundry is inPekanbaru City. While the population and samples use laundry businesses but onlyregistered laundry and consumers are harmed. Primary data sources and secondarydata. Data collection techniques in this study were interviews and literature studies.From the results of the study there are several problems that give rise to twopoints. First, the question is how the form of the implementation of the rights andobligations of the laundry businessman to consumers in the city of Pekanbaru is becausethere are many implementations of losses that are still not done properly. Second, whatare the barriers to the implementation of the responsibilities of laundry businesses toconsumers in the city of Pekanbaru that still business people feel some obstacles to theimplementation of responsibilities caused by consumers themselves.Suggestions the author, first, for laundry businesses should know what their rightsand obligations are in managing their business. Second, the authors hope consumers willbe more critical, both during the pre-transaction period, during the consumer transactionperiod, and at the end of the consumer transaction. Third, the author hopes that thegovernment should increase efforts to socialize Law No. 8 of 1999 concerning ConsumerProtection to the public, especially consumers and business actors.Keywords: Responsibilities - Business Actors - Consumers - Laundry